Plastic Inputs to Lake Rotorua: An Initial Assessment of Stormwater Stream Plastic Loads and Capture Devices - Aria Kerebs; Margaret Armstrong; Deniz Özkundakci (New Zealand Journal of Marine and Freshwater Research, 2026)
Plastics are a known but inconsistently researched challenge to Aotearoa New Zealand's inland freshwater systems. Understanding plastic origins, movement, and removal options for individual water bodies can enhance management efforts. This exploratory study quantified meso‐ and macroplastics entering Lake Rotorua through stormwater streams and assessed suitability of in‐stream capture devices. Plastic samples were collected and analysed over five sampling events at seven Rotorua city stormwater sites. Of the 306 samples (5982 g total), 51 were made of recyclable polymers, 124 were nonrecyclable and 131 were unidentifiable (e.g., degraded). Significant differences (ANOVA) were observed between the sample counts and weights of some sites (e.g., Depot Street and Headwater). With plastics present in the stormwater streams, capture devices are one option for collecting and removing pollution. A literature review was conducted to ascertain what aquatic‐based devices are being used globally and which are suitable for the stormwater streams. Six Rotorua‐based criteria (e.g., suitability in narrow or shallow channels) identified booms and boom‐receptable devices as recommended for trialling. Study findings can support reassessment of ongoing initiatives in Rotorua city and guide further scientific research. These insights can also be applied to meso‐ and macroplastic pollution in lakes with similar urbanised catchments.